The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1097/01.rhu.0000049712.74443.70
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Arthritis Associated with Thromboangiitis Obliterans

Abstract: Thromboangiitis obliterans (TAO) is an uncommon to rare vasculitis of small and medium arteries and veins typically affecting young male smokers. Inflammatory arthritis has only been rarely reported in association with TAO. We describe the case of a young male smoker presenting with inflammatory arthritis as the initial manifestation of his TAO. His arthritis resolved with a course of corticosteroid therapy. The vascular disease improved with hyperbaric oxygen therapy, although he continued to smoke. Similar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Moreover, corticosteroids and immunosuppressants, but not anti-thrombotic or vasodilator treatments, did improve the skin and joint manifestations of the disease whilst aggravating the limb ischemia and, in a case of mesenteric ischemia, led to perforation of the bowel, followed by death. 15 , 72 , 73 , 79 In terms of invasive treatments, bypass surgery had more acceptable outcomes in comparison to endovascular procedures, including stenting. However, more clinical evidence and clinical trials are needed to determine better management of patients with visceral TAO.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, corticosteroids and immunosuppressants, but not anti-thrombotic or vasodilator treatments, did improve the skin and joint manifestations of the disease whilst aggravating the limb ischemia and, in a case of mesenteric ischemia, led to perforation of the bowel, followed by death. 15 , 72 , 73 , 79 In terms of invasive treatments, bypass surgery had more acceptable outcomes in comparison to endovascular procedures, including stenting. However, more clinical evidence and clinical trials are needed to determine better management of patients with visceral TAO.…”
Section: Discussionmentioning
confidence: 99%
“…In ammation is signi cantly correlated with thrombogenesis, and thrombosis and vasculitis are major ganrenes in many systemic in ammatory diseases, such as TAO, antineutrophil cytoplasmic antibody (ANCA)-related vasculitis, Takayasu's arteritis, systemic lupus erythematosus, antiphospholipid syndrome (APS) and in ammatory bowel disease, etc [49,50]. Plenty of researches also showed that in ammation-associated cytokines, such as interleukin (IL)-1β, IL-4, IL-17, IL-23, IL-6 and Tumor necrosis factor-α (TNF-α) were associated with TAO [51][52][53][54]. In our study, we also certi ed that NP or MFS in combination with NDDM dramatically decreased IFN-γ, IL-1β, IL-6 and TNF-α levels, indicating that he combination of NP or MFS and NDDM inhibited in ammation-associated cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The pathology of TAO is inflammatory cell infiltration caused by vascular inflammation ( 17 ). Therefore, some scholars believe that TAO is a form of autoimmune inflammatory disease ( 18 ).…”
Section: Discussionmentioning
confidence: 99%